2018
DOI: 10.1111/jace.15779
|View full text |Cite
|
Sign up to set email alerts
|

(Hf0.2Zr0.2Ta0.2Nb0.2Ti0.2)C high‐entropy ceramics with low thermal conductivity

Abstract: A novel high‐entropy carbide ceramic, (Hf0.2Zr0.2Ta0.2Nb0.2Ti0.2)C, with a single‐phase rock salt structure, was synthesized by spark plasma sintering. X‐ray diffraction confirmed the formation of a single‐phase rock salt structure at 26‐1140°C in Argon atmosphere, in which the 5 metal elements may share a cation position while the C element occupies the anion position. (Hf0.2Zr0.2Ta0.2Nb0.2Ti0.2)C exhibits a much lower thermal diffusivity and conductivity than the binary carbides HfC, ZrC, TaC, and TiC, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
179
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 451 publications
(194 citation statements)
references
References 29 publications
11
179
2
2
Order By: Relevance
“…11b). Yan X et al 78 reported elastic (nanoindentation) and Vicker's hardness results for (Ti,Zr,Hf,Ta,Nb,Ta)C and found that they were comparable to those of the monocarbides reported in the literature. However, the HEC had a theoretical density of only 93%, which would have resulted in a relatively low Vicker's hardness.…”
Section: Mechanical Propertiesmentioning
confidence: 60%
See 1 more Smart Citation
“…11b). Yan X et al 78 reported elastic (nanoindentation) and Vicker's hardness results for (Ti,Zr,Hf,Ta,Nb,Ta)C and found that they were comparable to those of the monocarbides reported in the literature. However, the HEC had a theoretical density of only 93%, which would have resulted in a relatively low Vicker's hardness.…”
Section: Mechanical Propertiesmentioning
confidence: 60%
“…Yan et al 78 2 )O the distortion from an ideal rocksalt structure occurs primarily through disorder of the anion sublattice, which was conrmed by an extended X-ray absorption ne structure (EXAFS) analysis. 64 It is worth mentioning that the carbon stoichiometry of the samples was not analysed, which has an effect on the thermal conductivity due to phonon scattering by carbon vacancies.…”
Section: Thermal Conductivitymentioning
confidence: 99%
“…The present authors [28] have previously developed and utilized an ab initio entropy descriptor to synthesize nine different five-metal carbides, six of which formed single-phase high entropy materials that demonstrated high hardness values. Recent work done by Castle et al [29,30] [32], which demonstrated low thermal conductivity and a high elastic modulus and hardness.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2015, high-entropy ceramics (HECs) have been made in bulk form, including various high-entropy oxides [6][7][8][9][10], borides [11,12], carbides [13][14][15], nitrides [16], and silicides [17,18]. Unlike metallic HEAs of simple FCC, BCC or HCP structures, HECs typically only have high-entropy mixing at one (or multiple) cation sublattice(s).…”
Section: Introductionmentioning
confidence: 99%